'Erziehung' in erziehungswissenschaftlichen Lexika von 1895 bis 1989 - Stisser, Anna (Universitätsverlag Göttingen, 2021)
What does the discipline of educational science ,know' about ,education' - the term that stands unchallenged at the core of educational knowledge? The present study asks, on the one hand, about the bodies of knowledge on education that has been handed down in disciplinary lexicons from almost a hundred years and, on the other hand, about the discipline that becomes visible in this stored knowledge. The knowledge stocks contouring educational knowledge are examined serially on three levels. (1.) that of the framing lexicon, (2.) that of the lemma titles associated with ,education', and (3.) that of the explications' texts which specifically are devoted to the object of ,education'. In addition, (4.) the personal, textual and thematic reference spaces spanned in the explications are analyzed. The quantifying evaluation of the bodies of knowledge - such as lexical data and metadata, data in front of editors and authors, words, references, names, citations, and bibliographical references - is combined with a qualitative content-analytical reconstruction of knowledge configurations as they appear in prefaces and epilogues as well as in the explications of the educational lemmas. The project will elaborate the conjunctures, (dis)continuities, appropriations, and boundary markings of disciplinary knowledge on ,education' from 1895 to 1989 - a period in which German-language educational science institutionalized, established, specialized, and diversified itself as a university-based, researching discipline.